Shift work: it's association with physical and Psychosocial health among HUSM staff nurses - Yusuf, Azlina (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
INTRODUCTION: Health service is one of the industries which provide a continuous around the clock service, for the benefit of the community. Nurses as part of health care professional are required to work day and night to fulfill the needs of the sick. Shift works are commonly classified into rotating shifts, displaced work-hours and irregular shifts. Of the three categories of shift work, rotating shifts are of particular concern to nurses. The rotating schedule that they work may interfere with their normal biological or social diurnal rhythms or both. Shift work has been found to be associated with physical, psychological and social health problems. OBJECTIVES: The study was done to determine relationships between shift work with physical and psychosocial health symptoms among HUSM staff nurses. METHODS: This cross-sectional study involved 146 shift workers and 58 non-shift workers of HUSM nursing staff. Data was collected through self-administered questionnaire consisting of six parts which include demographic data, working condition, physical and psychosocial health status and the last part is a Malay version of Depression, Anxiety, Stress Scale (DASS 21 ). Chi-square test or Fisher Exact Test was performed to determine the significant difference of categorical variables between shift and non-shift workers. RESULTS: On physical health symptoms, there was association between shift work with reproductive problems. There was no association between problems of cardiovascular, gastrointestinal, menstrual regularity, general ill feelings and chronic fatigue syndrome among shift and non-shift staff nurses in HUSM. The prevalence of accidents and injuries among shift workers was higher than non-shift workers; however the difference was statistically not significant. On psychosocial health aspect, there was no significant difference in the sleep problems and disturbances that cause sleep difficulty between the shift and non-shift workers. Although there were no significant difference in the perceived quality of sleep among the two workers group but the value of poor sleep quality was higher amoog shift workers. There was a significant association between shift work and problems of child care, relationship with partners, depression and stress symptoms. CONCLUSION: There were associations between shift work and reproductive problems, problems with child care and relationship with partner as well as the symptoms of depression and stress among HUSM staff nurses. These issues require immediate remedial actions on the part of hospital and nursing administration.